Violation Of Children's Rights In Dave Pelzer's Trilogy: A Child Called It, The Lost Boy, And A Man Named Dave - Vianita Rosari, Dwi, Dr. M. Thoyibi, Drs., M.S, Dr. Phil. Dewi Candraningrum, M.Ed (2017)
Study on Violation of the Children has focused on abusive and exploitation to the children that violate the children's right convention by Unicef. The researcher uses qualitative method and the trilogy by Dave Pelzer: A Child Called "It", The Lost Boy, and A Man named Dave as object. The results of this research are there are 10 kinds of violation, they are inadequate food, inapropriate shelter, limited access to school, limited acess to play, leisure and relax, separation from parent, prohibition of cultural activities, abusive, exploitation, disregarding what he think, unprotected weakness. The depiction of children's right violation are creating character and characterization, creating setting of place , creating plot, creating point of view, and creating style. Then, the reason Dave Pelzer write the memoir is to inform to other that he is one of the child that had abused his mother and expect to other parent don't do that to their child. Then, he wants public aware that social workers is not just to earn money. Actually they work to care the children that have problem with their family well.